Ethnicity and detention: are Black and minority ethnic (BME) groups disproportionately detained under the Mental Health Act 2007? - Gajwani, Ruchika (Soc Psychiatry Psychiatr Epidemiol, 2016)
PURPOSE: There is substantial evidence to suggest that Black and minority ethnic (BME) patients are disproportionately detained under the Mental Health Act (MHA). We examined ethnic differences in patients assessed for detention and explored the effect of ethnicity after controlling for confounders. METHODS: A prospective study of all MHA assessments conducted in 1 year (April 2009–March 2010) within Birmingham and Solihull Mental Health Foundation Trust, UK. Proportion of assessments and detentions within denominator population of service users and regional populations were calculated. Multiple regression analysis was conducted to determine which variables were associated with the outcome of MHA assessment and the role of ethnicity. RESULTS: Of the 1115 assessments, 709 led to detentions (63.58 %). BME ethnic groups were statistically more likely to be assessed and detained under the MHA as compared to Whites, both in the service user and the ethnic population estimates in Birmingham, UK. MHA detention was predicted by having a serious mental illness, the presence of risk, older age and living alone. Ethnicity was not associated with detention under the MHA with age, diagnosis, risk and level of social support accounted for. CONCLUSION: The BME ‘disproportionality’ in detention rates seems to be due to higher rates of mental illness, greater risk and poorer levels of social support rather than ethnicity per se.